(untitled) (International Journal of Engineering and Computer Science, 2015)
The main aim of this paper is to design a wireless communication between helmet and the bike, so that the bike rider would mandatorily use his helmet, indeed to have a safe drive.In this paper, helmet plays a vital roleand so we named this device as INGENIOUS ARMOR, which is cleverly and originally devised to be well-suited for its purpose i.e.,for protection from death and head injuries.This paper is designed around a Microcontroller which forms the control unit of the project. According to this paper, the bike doesn’t ignite until and unless the bike rider wears the helmet. This is done by communication between helmet (transmitter) and the bike (receiver).In the same way, i.e., if the bike rider is in drunken state then also bike doesn’t get ignite. And if the person unfortunately meets with an accident then a message would be sent to his beloved family members, police, and ambulance in order to save a life to a possible extent. And the bike rider is indicated with a buzzer at wide curving’s or any accident prone areas and of school zones. The above two cases are carried with use GPS &GSM modules.